Closed (hydrodynamic) versus open (lateral sinus floor) subantral augmentation for single tooth replacement: criteria of decision-making and clinical efficacy - Artemchuk Artem; Yahodka Bohdan; Osmanov Bekir; Kopchak Andrii; Chepurnyi Yurii (Journal of Oral Medicine and Oral Surgery)
Introduction: This research aimed to study the impact of initial anatomical conditions on decision-making for subantral augmentation in a single tooth gap and to compare the clinical efficiency of closed hydrodynamic sinus lift and lateral sinus floor augmentation (LSFA) for single tooth restoration. Materials and Methods: This retrospective study included 96 patients who underwent subantral augmentation with simultaneous implantation in a single tooth gap. Patients were divided: 50 in the “Open” LSFA group and 46 in the “Closed” hydrodynamic lift group. A two-stage protocol was applied, with data on age, intervention site, implant dimensions, and bone height analyzed. Results: Mean residual bone height differed: 3.341 ± 1.433 mm in “Open” and 4.437 ± 1.741 mm in “Closed” (p = 0.001). Median bone height post-surgery was 9.5 mm in “Open” and 8.5 mm in “Closed” (p = 0.0031), with significant bone height increase (p < 0.00001). No implant or graft removals were needed. Conclusion: Residual alveolar ridge height, cortical bone thickness, and sinus wall thickness are key criteria in selecting a protocol. Both techniques achieved effective results, even with initial bone heights below 5 mm. LSFA led to greater bone height increase, while both approaches provide reliable options for stable implant integration.